2023
DOI: 10.3847/1538-4357/acd934
|View full text |Cite
|
Sign up to set email alerts
|

Extragalactic Magnetism with SOFIA (SALSA Legacy Program). V. First Results on the Magnetic Field Orientation of Galaxies

Abstract: We present the analysis of the magnetic field (B-field) structure of galaxies measured with far-infrared (FIR) and radio (3 and 6 cm) polarimetric observations. We use the first data release of the Survey of extragALactic magnetiSm with SOFIA of 14 nearby ( < 20 Mpc) galaxies with resolved ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 118 publications
2
9
0
Order By: Relevance
“…The reason for this difference may be caused by the interaction of M51 with M51b (NGC 5195) and/or the injection of kinetic energy driven by the region of strong star formation in the outskirts of the spiral arms of M51. These results have been further confirmed using a sample of seven spiral galaxies with FIR and radio polarimetric observations (Borlaff et al 2023). The difference in the observed B-field structure arises from the different nature of the interstellar medium (ISM) associated with the FIR and radio wavelengths.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The reason for this difference may be caused by the interaction of M51 with M51b (NGC 5195) and/or the injection of kinetic energy driven by the region of strong star formation in the outskirts of the spiral arms of M51. These results have been further confirmed using a sample of seven spiral galaxies with FIR and radio polarimetric observations (Borlaff et al 2023). The difference in the observed B-field structure arises from the different nature of the interstellar medium (ISM) associated with the FIR and radio wavelengths.…”
Section: Introductionmentioning
confidence: 62%
“…Far-infrared (FIR) polarimetric observations have revealed different components of the large-scale B-fields in the disk of galaxies (e.g., Borlaff et al 2021Borlaff et al , 2023Lopez-Rodriguez et al 2021. The detailed study performed in the spiral galaxy M51 showed that the radio and FIR magnetic pitch angles are similar within the central 6 kpc, but at larger radii Ψ B is wrapped tighter at FIR than at radio wavelengths (Borlaff et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that the B-field orientation of M 82 at 89 and 850 μm is predominantly parallel to the galactic outflow with a secondary component parallel to the galaxy disk at galactocentric radius >1 kpc. The B-fields in the outflows have also been reported (Lopez-Rodriguez et al 2021, 2022bBorlaff et al 2023) within the range of 53-214 μm for M 82 and NGC 2146. These results are quite extraordinary because they show that magnetically aligned dust grains are present in the CGMaround starburst galaxies up to scales of several kpc.…”
Section: Introductionmentioning
confidence: 66%
“…The lines show the E-vectors with the 10% polarization legend shown in the bottom lefthand corner. FIR polarimetry observations reliably trace the B-fields in the galactic outflows (middle panel) (Jones et al 2019;Lopez-Rodriguez et al 2021;Borlaff et al 2023). Radio polarimetric observations have short lifetime cosmic rays along the galactic outflow and only a magnetized bar is measured (right-hand panel) (e.g., Thompson et al 2006;Adebahr et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation